O28 Factors associated with preferences for in-person versus remote consultations for IBD: a UK-wide online survey. (19th June 2022) - Bodger, Keith; Taylor, Frederick; Dobson, Elizabeth; Bunn, Judith; Grainger, Stephen; Cummings, Fraser; Bloom, Stuart; Kennedy, Nick
Abstract : Introduction: The COVID-19 pandemic resulted in a forced shift to providing remote (telephone and online) consultations following disruptions to traditional in-person care. As the pandemic wanes and IBD services recover, there is a need to rebalance provision of care and align with patient preference rather than provider convenience. Better knowledge of preferences for remote versus in-person care among people with IBD, and of the factors associated with such preferences, will guide this realignment. We report the results of a large-scale, UK-wide follow-up survey of patients who had completed the COVID-19 IBD Risk Tool during the early pandemic. 1 Methods: Adult patients who consented for research (n=35, 329) were invited by e-mail. The survey included sociodemographics, place of residence, self-reported diagnosis, drug treatments, PRO-2 symptoms, IBD-Control Questionnaire and items relating to experience of, and future preference for, mode of IBD consultations. We investigated factors associated with: 'In-person preference ' for future consultations (response option: 'Never by telephone or video' versus all other options); and 'Remote preference ' (response: 'Mainly by telephone or video' versus all others) in bivariate and multivariable binary logistic regression analyses, with results expressed as adjusted odds ratios (aOR) and 95% CI. Results: 7, 341 respondents of which 6, 015 (82%) had experienced a remote IBD consultation since the first UK lockdown. Of these, 4, 396 (73%) said their first experience of a remote consultation was during the pandemic. A significant minority (9.6%) would prefer to avoid future remote consultations entirely (in-person preference) whereas a quarter (24.5%) wished to have mainly remote consultations (remote preference). The following factors were associated with in-person preference (aOR [95% CI]): Older age (>50 years; 1.40 [1.19–1.63]), male gender (1.31 [1.11–1.53]), less-well controlled disease (IBD-Control-8 score <13, 2.06 [1.74–2.45]), and residents of more deprived areas (Quintile 5 [most deprived]; 1.72 [1.31–2.25] vs Quintile 1 [least deprived]). Conversely, we found the following associations for remote preference: Younger age (<50 years; 1.24 [1.12–1.39]), Ulcerative Colitis or IBD-U (1.23 [1.10–1.37]), well-controlled disease (IBD-Control-8 score 13+, 1.55 [1.38–1.73]), not having sought emergency care during the pandemic (1.21 [1.06–1.37]) and living in least deprived areas (Quintile 1; 1.29 [1.05–1.59] vs Quintile 5). Conclusions: A number of sociodemographic and clinical variables predicted future consultation preference at the time of survey. These included relatively fixed characteristics (e.g. age, gender, diagnosis, and deprivation status) and more dynamic factors (e.g. current disease control). Better understanding of factors associated with patient preference can inform efforts to realign services to provide the right mix of in-person and remote provision. Reference: https://ibdregistry.org.uk/covid-19/